Personalization technical and tactical training of qualified judokas. - Shishlova Darya Viktorovna (Kharkov National Pedagogical University, 2011)
Systematized the literature regarding individual technical and tactical training of qualified judo wrestlers. A system for individualizing the technical and tactical training in women's judo. Highlighted the main provisions of individualization of technical and tactical training of qualified judo wrestlers. Certainly the structure of individualization process of preparing athletes. A pattern of dynamics of individual functional state. Developed interactive technology to improve the individualization of the training process.